Fundamentalism and Education in the Scopes Era - Laats, A. author. aut Link
IX, 258 p.
Keywords: This book takes a new look at one of the most contentious periods in American history. The battles over schools that surrounded the famous Scopes "monkey" trial in 1925 were about much more than evolution. Fundamentalists fought to maintain cultural control of education. As this book reveals for the first time, the successes and the failures of these fundamentalist campaigns transformed both the fundamentalist movement and the nature of education in America. In turn, those transformations determined many of the positions of the "culture wars" that raged throughout the twentieth century.